Multidimensional Family Therapy (MDFT) for Young People in Treatment for Non‐opioid Drug Abuse: A Systematic Review. Issue 1 (2nd March 2015) - Filges, Trine; Rasmussen, Pernille Skovbo; Andersen, Ditte; Jørgensen, Anne‐Marie Klint
Abstract : This publication is a Campbell Systematic Review of the effect of Multidimensional Family Therapy (MDFT) for treating abuse of cannabis, amphetamine, ecstasy or cocaine (referred to here as non‐opioid drugs) among young people aged 11‐21 years. The misuse of prescription drugs and the use of ketamine, nitrous oxide and inhalants such as glue and petrol are not considered in this review. After a rigorous search of the literature, five randomized controlled studies with samples of 83‐450 participants were identified. Three studies were conducted by MDFT program developers, one study was conducted by an independent investigator with the program developer as a co‐author, and one study was conducted by independent investigators. Four studies were performed in the US, while the other was performed across five European countries. There is evidence that MDFT is slightly more effective in treating young people's drug abuse than other treatments; however, the difference is small. Furthermore, none of the five included studies could be characterised as a robust randomised controlled trial with a low risk of bias on all assessed domains. One study provided insufficient information on core issues for the risk of bias to be assessed and therefore we find reason to question the validity of this study. Well‐designed, randomized controlled trials within this population are needed. More research is also required to identify factors which modify the effect of MDFT and to identify which particular youth subgroups may be most likely to respond. Key messages: PLAIN LANGUAGE SUMMARY: This publication is a Campbell Systematic Review of the effect of Multidimensional Family Therapy (MDFT) for treating abuse of cannabis, amphetamine, ecstasy or cocaine (referred to here as non‐opioid drugs) among young people aged 11‐21 years. The misuse of prescription drugs and the use of ketamine, nitrous oxide and inhalants such as glue and petrol are not considered in this review. Youth drug abuse is a severe problem worldwide and recent reports describe ominous trends of youth drug abuse and a lack of effective treatment. This review is concerned with drug abuse that is severe enough to warrant treatment. It focuses on young people who are receiving MDFT specifically for non‐opioid drug abuse. MDFT is a manual‐based, family‐oriented treatment, designed to eliminate drug abuse and associated problems in young people's lives. MDFT takes a number of risk and protective factors into account; the approach acknowledges that young people's drug abuse is linked to dimensions such as home life, friends, school and community (Liddle et al., 2004). MDFT aims to modify multiple domains of functioning by intervening with the young person, family members, and other members of the young person's support network (Austin et al., 2005). MDFT is thus based on a number of therapeutic alliances, with the young drug abuser, his or her parents and other family members, and sometimes with school and juvenile justice officials. After a rigorous search of the literature, five randomized controlled studies with samples of 83‐450 participants were identified. Three studies were conducted by MDFT program developers, one study was conducted by an independent investigator with the program developer as a co‐author, and one study was conducted by independent investigators. Four studies were performed in the US, while the other was performed across five European countries. We used meta‐analytic procedures to summarise the available evidence on the effects of MDFT in comparison with other interventions on drug abuse, education, family functioning, risk behavior and retention in treatment. In this review, we interpret a value of the standardised mean difference, SMD=0.20 as a small effect size, in line with the general practice (Cohen, 1988). We note, however, the possibility that such a value might actually represent a larger effect if it is equivalent to a large reduction in the percentage of days a youth uses drugs, but we cannot comment further as we were unable to analyse the absolute effect of MDFT given that no studies comparing MDFT to no other treatment were available. The findings are as follows: – On drug abuse: Based on the available evidence we conclude that MDFT has an effect on drug abuse reduction compared to other treatments, although the difference is small. – On education: There is insufficient evidence to conclude whether MDFT has an effect on education compared to other treatments. – On family functioning: There is no available evidence to conclude whether MDFT has an effect on family functioning compared to other treatments. – On risk behavior and other adverse effects: There is no available evidence to conclude whether MDFT has an effect on risk behavior and other adverse effects compared to other treatments. – On treatment retention: MDFT may result in improved treatment retention in young drug abusers compared to other interventions The evidence found was limited as only five studies were included, and two studies had significant amounts of missing data. The evidence was very limited in terms of the outcomes reported on education, family functioning and risk behavior, and was insufficient for firm conclusions to be drawn on the effectiveness of the treatment with regard to such outcomes. There is evidence that MDFT is slightly more effective in treating young people's drug abuse than other treatments; however, the difference is small. Furthermore, none of the five included studies could be characterised as a robust RCT with a low risk of bias on all assessed domains. One study provided insufficient information on core issues for the risk of bias to be assessed and therefore we find reason to question the validity of this study. Well‐designed, randomized controlled trials within this population are needed. More research is also required to identify factors which modify the effect of MDFT and to identify which particular youth subgroups may be most likely to respond. Executive summary/Abstract: BACKGROUND: Youth drug abuse is a severe problem worldwide, and the use of cannabis, amphetamine, ecstasy and cocaine (referred to here as non‐opioid drugs) is strongly associated with a range of health and social problems. This review focuses on drug abuse that is severe enough to warrant treatment. The population of interest is young people who are receiving MDFT specifically for non‐opioid drug abuse. MDFT is a manual‐based family therapy approach that focuses on individual characteristics of the young person, the parents, and other key individuals in the young person's life, as well as on the relational patterns contributing to the drug abuse and other problem behaviors. A variety of therapeutic techniques are used to improve the young person and the family's behaviors, attitudes, and functioning across the variety of domains. MDFT aims to reorient the young person and his/her family towards a more functional developmental trajectory based on key principles that include: 1) Individual biological, social, cognitive, personality, interpersonal, familial, developmental, and social ecological aspects can all contribute to the development, continuation, worsening and chronicity of drug problems; 2) The relationships with parent(s), siblings and other family members are fundamental domains of assessment and change; 3) Change is multifaceted, multi‐determined and relates to the youths' cognitive and psychosocial developmental stages; 4) Motivation is not assumed, but is malleable; and motivating the young person and his or her family members about treatment participation and change is a fundamental therapeutic task; 5) Multiple therapeutic alliances are required to create a foundation for change; and 6) Therapist responsibility and attitude is fundamental to success (Liddle, 2010). OBJECTIVES: The main objectives of this review are to evaluate the current evidence on the effects of MDFT on drug abuse reduction for young people (aged 11‐21 years) in treatment for non‐opioid drug abuse, and if possible to examine moderators of drug abuse reduction effects, specifically analysing whether MDFT works better for particular types of participants. SEARCH STRATEGY: An extensive search strategy was used to identify qualifying studies. Searches were run in October 2014. A wide range of electronic bibliographic databases were searched along with government and policy databanks, grey literature databases, citations in other reviews and the included primary studies, hand searching in relevant journals, and Internet searches using Google. We also maintained correspondence with researchers in the field of MDFT. No language or date restrictions were applied to the searches. SELECTION CRITERIA: To be eligible for inclusion, studies must: have involved a manual‐based outpatient MDFT drug treatment for young people aged 11‐21 years enrolled for non‐opioid drug abuse; have used experimental, quasi‐experimental or non‐randomized controlled designs; have reported at least one of the following eligible outcome variables: abstinence, reduction of drug abuse, family functioning, education or vocational involvement, retention, risk behavior or any other adverse effect; not have focused exclusively on treating mental disorders; and have had MDFT as the primary intervention. DATA COLLECTION AND ANALYSIS: The literature search yielded a total of 6, 519 references, of which 170 studies were deemed potentially relevant and retrieved for eligibility determination. Of these, 16 papers describing five unique studies were included in the final review. Metaanalysis was used to examine the effects of MDFT on drug usage (measured by both frequency and problem severity), on education and on treatment retention. It was not possible to perform a meta‐analysis on family functioning, risk behavior or other adverse effects, nor was it possible to assess moderators of drug abuse reduction effects, or whether MDFT works better for particular types of participants. RESULTS: Not all the studies provided data that enabled the calculation of comparable effect sizes on the different outcomes. Two studies had two comparison groups with different individuals, and we performed separate analyses including the different control groups where these two studies provided relevant outcome measures. The most conservative effects for the different outcomes are reported in the following. All outcomes are measured as decreases; hence a negative effect size favours MDFT. Meta‐analysis of the five included studies showed a small effect (around 30 percent of a standard deviation for the different control combinations) of MDFT for reduction in youth drug abuse problem severity at 6 months post‐intake (SMD=‐0.30 (95% CI ‐0.53 to ‐0.07, p=0.01 compared to Cognitive Behavioral Therapy (CBT), peer group, treatment as usual (TAU), multifamily educational therapy (MEI) and Adolescent Community Reinforcement Approach (ACRA)). At 12 months post‐intake meta‐analysis of the five included studies showed a small effect (around 20 percent of a standard deviation for the different control combinations) of MDFT for reduction in youth drug abuse problem severity (SMD=‐0.23 95% CI ‐0.39 to ‐0.06, p=0.007 compared to CBT, peer group, TAU, adolescent group therapy (AGT) and ACRA). Pooled results of the four studies providing data on drug abuse frequency reduction favoured MDFT. The effect of MDFT for youth drug abuse frequency reduction was small at 6 months post‐intake (overall around 20 percent of a standard deviation for the different control combinations) (SMD = ‐0.24; 95% CI ‐0.43 to ‐0.06; p=0.01 compared to CBT, peer group, TAU and MET/CBT5). It was not statistically significant at 12 month follow‐up compared to CBT, peer group, TAU and MET/CBT5/ACRA. Two studies reported on school grades as an outcome, providing data at 6 months post‐intake only. Meta‐analysis favored MDFT when the controls used in the analysis were peer group and MEI (SMD = ‐0.47; 95% CI ‐0.92, ‐0.01; p=0.05). It was not statistically significant when the comparisons used in the analysis were peer group and AGT. We extracted data on retention from all five included studies. Meta‐analysis favoured MDFT for retention of participants for all the different control combinations (OR = 0.44; 95% CI 0.21 to 0.94; p=0.03 compared to CBT, peer group, TAU, AGT and MET/CBT5). Overall the results indicated that retention may be positively affected by structured MDFT treatment compared to less structured control conditions. AUTHORS' CONCLUSIONS: The available data support the hypothesis that, compared with certain other active treatments, MDFT reduces the severity of drug abuse among youth. The treatments MDFT was compared against in the included studies were Cognitive Behavioral Therapy (CBT), peer group, treatment as usual (TAU), adolescent group therapy (AGT)/multifamily educational therapy (MEI) and Motivational Enhancement Therapy/Cognitive Behavioral Therapy (MET/CBT5)/Adolescent Community reinforcement approach (ACRA). Furthermore, the available data support the hypothesis that there is a reduction in the frequency of drug abuse when treating young drug abusers with MDFT compared to CBT, peer group, TAU and MET/CBT5/ACRA at 6 months post‐intake, but the effect is not statistically significant 12 months after intake. The number of studies providing data that allowed calculation of an effect size for drug abuse reduction was limited, however, and this should be considered when interpreting these results. The conclusions that can be drawn about MDFT as an effective treatment for young drug abusers compared to other treatments would be more convincing if more studies were available. The pooled effect sizes are small and confidence intervals are often close to zero. The statistically significance of the pooled results on severity of drug abuse among youth 6 months post‐intake is sensitive to the removal of studies with methodological weaknesses. Overall, the results also indicate that retention may be positively affected by structured MDFT treatment compared to CBT, peer group, TAU, AGT/MEI and MET/CBT5/ ACRA which are all less‐structured control conditions. However, the results must be interpreted with caution as two studies stand out from the others; here the effect sizes are large, confidence intervals are wide, and the estimated between study variation is relatively large. The main conclusion of this review is that there is insufficient firm evidence of the effectiveness of MDFT, especially with regard to moderators of drug abuse reduction effects, and whether MDFT works better for particular types of participants. While additional research is needed, the review does, however, offer support that MDFT treatment to young non‐opioid drug abusers reduce their drug abuse somewhat more than CBT, peer group, TAU, AGT/MEI and MET/CBT5/ACRA.